Pengaruh Praktik Kerja Industri, Bimbingan Karir, Motivasi Memasuki Dunia Kerja dan Soft Skill terhadap Kesiapan Kerja (Jurnal Simki Pedagogia, 2024)
Examining the influence of industrial work practice, career counseling, encouragement to enter the world of work, and soft skills on work preparation is the purpose of this study. The research population was all XII grade students of SMK N 5 Palembang totaling 400 people, a research sample of 129 was determined through the G*power program, data collection techniques using questionnaires and multiple regression (ARM) with the backward method assisted by SPSS 26 for data analysis. The test results for the R coefficient of multiple regression models provide a test statistical value of F = 27.148, and a p-value (Sig.)